Pharmacokinetic/Pharmacodynamic Interaction Between Evogliptin and Pioglitazone in Healthy Male Subjects - Hwang I; Kim Y; Yoo H; Jang IJ; Yu KS; Lee S (Dove Medical Press, 2020)
Inyoung Hwang, Yun Kim, Hyounggyoon Yoo, In-Jin Jang, Kyung-Sang Yu, SeungHwan Lee Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Republic of KoreaCorrespondence: SeungHwan LeeDepartment of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, 101 Daehak-ro, Jongno-gu, Seoul 03080, Republic of KoreaTel +82-2-2072-2343Fax +82-2-742-9252Email leejh413@snu.ac.krAim: Evogliptin is a newly developed oral glucose-lowering medication of the dipeptidyl peptidase 4 (DPP-4) inhibitor class for type 2 diabetes mellitus. The combination of a DPP-4 inhibitor with pioglitazone is a promising therapeutic option. The aim of the present study was to evaluate the pharmacokinetic and pharmacodynamic interaction between evogliptin and pioglitazone.Materials and Methods: A randomized, open-label, multiple-dose, three-treatment, three-period, six-sequence crossover study was conducted in healthy Korean male subjects. All subjects received evogliptin 5 mg once daily for 7 days (EVO), pioglitazone 30 mg once daily for 7 days (PIO) and co-administration of evogliptin 5 mg and pioglitazone 30 mg once daily for 7 days (EVO+PIO) according to the assigned sequence and period. Serial blood samples were collected for 24 hours for pharmacokinetic analysis and 3 hours after the oral glucose tolerance test for the pharmacodynamic analysis.Results: Thirty-four subjects completed the study. EVO+PIO and EVO showed a similar maximum plasma concentration at steady state (Cmax,ss) and area under the concentration-time curve during the dosing interval at the steady state (AUCτ,ss) of evogliptin, with geometric mean ratios (GMRs) (90% confidence interval (CI)) of 1.01 (0.97– 1.05) and 1.01 (0.98– 1.04), respectively. EVO+PIO and PIO showed a similar Cmax,ss and AUCτ,ss of pioglitazone, with GMRs (90% CI) of 1.07 (0.99– 1.17) and 1.08 (0.99– 1.17), respectively. Reduction of the glucose level after EVO+PIO was larger compared to PIO and similar with EVO.Conclusion: Concomitant administration of evogliptin and pioglitazone showed similar glucose-lowering effects with those of evogliptin alone without pharmacokinetic interactions when compared to the intake of each drug alone.Keywords: evogliptin, pioglitazone, pharmacokinetics, pharmacodynamics, drug interaction